Fused π-extended truxenes via a threefold borylation as the key step - Zhang, Gang; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2016)
On the basis of a threefold borylated truxene, which is accessible in high yields by iridium-catalyzed borylation under CH-activation, fused π-extended truxenes have been synthesized by a two-step method of first Suzuki-Miyaura cross-coupling reaction and subsequent condensation reaction. The mild condensation method tolerates the presence of a variety of functional groups, such as nitro, fluoro, or carboxyl moieties. Furthermore, by using this approach, N- and S-heteroarene analogues become accessible for the first time, as well as larger structures that represent derivatives of precursors for fullerene C60 or buckybowls. The attached tert-butyl groups make all derivatives sufficiently soluble to allow full spectroscopic and electrochemical investigations. Postfunctionalization of selected derivatives for further synthetic applications of the compounds is also presented.
Gesehen am 04.10.2021